2017
DOI: 10.1186/s13071-017-2049-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and tolerance of imidocarb dipropionate versus atovaquone or buparvaquone plus azithromycin used to treat sick dogs naturally infected with the Babesia microti-like piroplasm

Abstract: BackgroundPiroplasmosis caused by the Babesia microti-like piroplasm (Bml) is increasingly being detected in dogs in Europe. Sick dogs show acute disease with severe anaemia associated with thrombocytopenia with a poor response to current available drugs. This study assesses the safety and tolerance of three treatments and compares their efficacy over a full year of follow up in dogs naturally infected with Bml.MethodsFifty-nine dogs naturally infected with Bml were randomly assigned to a treatment group: imid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Treatment with atovaquone (13.5 mg/kg PO q8h) and azithromycin (10 mg/kg PO q24h) for 10 days was recommended for all dogs as soon as the B. vulpes infection was diagnosed. Follow‐up data were available for 9 dogs, all of which were clinically improved after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with atovaquone (13.5 mg/kg PO q8h) and azithromycin (10 mg/kg PO q24h) for 10 days was recommended for all dogs as soon as the B. vulpes infection was diagnosed. Follow‐up data were available for 9 dogs, all of which were clinically improved after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Although limited information was available, we observed that dogs infected with B. vulpes , with or without concurrent B. gibsoni infection, exhibited a range of laboratory abnormalities similar to those previously reported with other Babesia spp. infections, including regenerative anemia, thrombocytopenia, hyperglobulinemia, hypoalbuminemia, and proteinuria. Azotemia, although previously reported as a common complication for dogs infected with B. vulpes in Europe, was not common in the dogs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…in vitro and in vivo in hamsters (Hughes and Oz, 1995 ; Wittner et al, 1996 ; Matsuu et al, 2008 ). In dog and human studies, combination with the antibiotic azithromycin turned out to be positive (Krause et al, 2000 ; Birkenheuer et al, 2004 ; Di Cicco et al, 2012 ; Checa et al, 2017 ). Treatment of L. donovani infections in a mouse model were less successful resulting only in a 30% lower parasite burden (Croft et al, 1992 ).…”
Section: Targeting Transport Processes Of Parasites At Different Levementioning
confidence: 99%
“…It is approved for treatment of different forms of Babesia spp. [39,57,63]. The adverse effects of this medication include pain during injection and cholinergic effects such as salivation, drooling, nasal drip or vomiting which can be mitigated by premedicating with atropine at 0.05 mg/kg.…”
Section: Therapymentioning
confidence: 99%
“…Buparvaquone (Butalex ® ) is used in the treatment of bovine theileriosis [69]. It is also used to treat B. vulpes infection in dogs at an off-label dose of 5 mg/kg IM twice 48 h apart, in combination with azithromycin at 10 mg/kgPO once daily for 10 days [63]. Buparvaquone's mode of action on piroplasms is probably comparable to atovaquone's.…”
Section: Combination Therapiesmentioning
confidence: 99%